2021
DOI: 10.5114/dr.2021.110798
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in the Gdansk area in Poland

Abstract: Introduction:Onychomycosis is a cutaneous fungal infection of the nail apparatus that is observed worldwide and represents about 50% of all nail disorders. The knowledge of prevalence and causative species of onychomycosis can accelerate its diagnosis and treatment. Over the last decades the incidence rate of cutaneous fungal infections and onychomycosis has been steadily increasing because of many factors such as aging population, increased antibiotics use and higher exposure to fungal species. Objective: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%